The formula of exchange value: the formal demonstration of sociability work in the capital of Karl Marx - Teixeira Filho, Francisco Luciano (Discusiones Filosóficas, 2013)
This article is dedicated to demonstrate the sociability of the work in the first section of: The capital, by means of establishing the formula of the exchange value in the commodity form of capital. Through deductions, from the conclusions of Marx, we developed a formula capable of expressing the exchange value. We concluded, by means of analyzing the proposed formula, that the sociability of the work is expressed in the singularization of the social work, in the product of individual work. That is, social work determines the equivalence between commodities, although the work that produces commodities is a singular work. Thus, we obtained the conclusion that the individual producer is a social means, whose work product is a product mediated by social work.